WIP transcriptional regulators modulate developmental progression in both life cycle phases of a moss - Maria Victoria Gomez Roldan; Yuhang Yan; Yujuan Du; Florence Charlot; Pierre-François Perroud; Julie Calbry; Ofir Griess; Marion Verdenaud; Fabien Marcel; Sylvie Citerne; Joseph Tran; Nir Ohad; et al. (Proceedings of the National Academy of Sciences, 2026)
The sexual life cycle of bryophytes and vascular plants, the two extant lineages of land plants, is dominated by a gametophytic and a sporophytic phase, respectively. Body plan diversification in these two phases has followed separate evolutionary trajectories in both lineages. However, how evolutionary conserved gene families have accompanied body plan diversification remains poorly understood. WIP transcription factors are conserved in land plants, and their function has been associated with root and flower development in angiosperms. Here, we dissect the function of Pp WIP1 and Pp WIP2 genes in a model bryophyte, the moss Physcomitrium patens . We demonstrate that Pp WIP s are expressed during both phases of the life cycle and regulate specific developmental processes. In the gametophytic phase, Pp WIP s promote the chloronema-to-caulonema transition, but restrict gametophore development. In the sporophytic phase, Pp WIPs prevent polysety, the formation of multiple sporogonia. RNA-seq, DAP-seq, and hormone analysis revealed that both P. patens and A. thaliana proteins act by controlling auxin homeostasis. Interspecies complementation experiments revealed that Pp WIP s are partially able to substitute At WIP molecular function in Arabidopsis root and seeds. Our findings demonstrate that WIPs control developmental progression in both phases of the land plant life cycle through an evolutionarily conserved molecular function.